The role of MRO as an M2 macrophage-associated gene in non-small cell lung cancer: insights into immune infiltration, prognostic significance, and therapeutic implications - Yue Gu; Miaosen Zheng; Jing Xie (Discover Oncology)
Abstract Background Non-small cell lung cancer (NSCLC), including lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC), is influenced by tumor-immune interactions. M2 macrophages play a significant role in the tumor microenvironment. This study explores the role of MRO, an M2 macrophage-associated gene, in NSCLC, focusing on immune infiltration, prognostic significance, and therapeutic potential. Methods NSCLC samples from The Cancer Genome Atlas (TCGA) were analyzed using the CIBERSORT algorithm to quantify immune cell compositions. Differential gene expression and correlation studies examined MRO’s association with M2 macrophages. Univariate Cox regression and Kaplan–Meier analyses assessed prognostic significance. Single-cell RNA sequencing data from TISCH2 evaluated MRO expression in different cell types. The ESTIMATE algorithm analyzed correlations between MRO expression and immune scores, while TIDE and Submap analyses predicted immunotherapy responses. Results MRO was highly expressed in NSCLC, particularly in LUAD and LUSC, and associated with M2 macrophages. MRO correlated with key immune pathways, including TNFα signaling via NFκB, inflammatory response, and IL6 JAK STAT3 signaling. High MRO expression correlated with poorer overall survival (OS) and disease-specific survival (DSS). Single-cell analysis confirmed MRO expression in macrophages. The ESTIMATE algorithm showed positive correlations between MRO expression and immune scores. TIDE and Submap analyses suggested low MRO expression in LUSC patients might predict better immunotherapy responses. Conclusions MRO is a critical M2 macrophage-associated gene in NSCLC, influencing immune infiltration and prognosis. It may serve as a biomarker for prognostication and a target for therapeutic intervention in NSCLC.